Kawasaki disease involving both the nervous system and cardiovascular system: a case report and literature review - Yin, Wen; Wu, Yali; Wang, Shasha; Tang, Hongxia; Ding, Yan (Frontiers in Pediatrics, 2024)
Background: Kawasaki disease (KD), an acute self-limiting vasculitis, is the main cause of acquired heart disease. Timely diagnosis and treatment can mitigate the occurrence of complications and improve patient prognosis. Facial nerve paralysis (FNP) and ptosis are rare complications of KD and are rarely reported, but FNP is considered a high risk factor for coronary aneurysms. If giant coronary artery aneurysms are formed, clinicians should be vigilant when diagnosing the formation of systemic artery aneurysms (SAAs).Patient presentation: A 10-month-old girl with fever, diffuse rash, and conjunctival congestion was hospitalized locally, diagnosed with KD, and treated with intravenous infusion of gamma globulin (IVIG). She had fever again after 1 week of temperature stability, accompanied by conjunctival congestion, and was treated with a second dose of IVIG, but she still experienced recurrent fever. The day prior to admission, she developed facial asymmetry, left FNP, diffuse erythema and membranous peeling of the fingers of both hands. The patient's body temperature normalized after treatment with 20 mg/kg methylprednisolone, but cardiac ultrasound revealed progressive enlargement of the coronary artery aneurysms. On day 37of the illness, transient eyelid ptosis developed; fortunately, the left FNP and eyelid ptosis finally resolved, leaving no sequelae. Two years and eight months after onset, the patient developed bilateral humeral aneurysm.This is the first KD patient involving two neurological complications combined with giant coronary artery aneurysms and SAAs. KD needs to be considered in infants with unexplained recurrent fever who present with FNP or ptosis. FNP secondary to KD is a high risk factor for coronary artery aneurysms, so it is necessary to perform cardiac ultrasound for accurate diagnosis. KDs combined with giant coronary aneurysms require careful physical examination and noninvasive angiography during follow-up to detect SAA formation.